Excess death estimates compared with state-reported and observed COVID-19 deaths, New Jersey and the United States, 2020–2022 - Reichbind, Diana; Mehari, Lemlem; Ojo, Mojisola; Bayoumi, Nagla; Lifshitz, Edward (Frontiers in Public Health, 2024)
Deaths associated with COVID-19 in the United States are currently estimated to be over 1.2 million, but the true mortality burden due to the SARS-CoV-2 virus is unknown. Methods for identifying and reporting deaths related to COVID-19 differ between jurisdictions, and concerns about overreporting and underreporting exist. Excess death estimates for the pandemic period, based on data from the National Center for Health Statistics, may be used to approximate the number of COVID-19-associated deaths. In this analysis, we describe the process by which the New Jersey Department of Health identified, classified, and reported COVID-19-associated deaths from January 2020 through December 2022. Then the National Center for Health Statistics’ excess deaths estimates are first compared with New Jersey's reported COVID-19-associated deaths, and then with the observed COVID-19-associated deaths in the entire United States, by month, from January 2020 through December 2022. New Jersey’s reported COVID-19-associated deaths (n=35,555) accounted for (and slightly exceeded) the state’s excess deaths estimated by the National Center for Health Statistics for 2020 to 2022 (n=30,365). However, the overall number of United States observed COVID-19 deaths for 2020 through 2022 (n=1,094,230) did not account for all estimated excess deaths in the nation for the same period (n=1,233,366). The general congruence of New Jersey’s reported COVID-19 deaths and the National Center for Health Statistics’ excess death estimates may be due in part to New Jersey’s early detailed classification system for identifying and reporting deaths associated with COVID-19, leading to more accurate COVID-19 death reporting by the state.